CONSTRUCTION OF AN ISLAMIC RELIGIOUS EDUCATION E-MODULE BASED ON THE NOTION PLATFORM AS A MEANS OF INCREASING STUDENT LEARNING MOTIVATION AND INDEPENDENCE - Sandi Pratama; Ana Fitriani; Asmaul Husna; Nurul Fahmi (Referensi Islamika: Jurnal Studi Islam, 2026)
This study aims to develop a Notion-based Islamic Religious Education e-module and examine changes in students’ learning motivation, learning independence, and perceived ease of use after its implementation. This study employed a Research and Development approach using the ADDIE model, which consists of analysis, design, development, implementation, and evaluation stages. The research was conducted at Muhammadiyah 1 High School Makassar and involved 61 students in grades X and XI. Data were collected through observation, questionnaires, interviews, and documentation. A five-point Likert scale questionnaire was administered before and after the implementation of the e-module. The data were analyzed using descriptive statistics, paired sample t-tests, linear regression, and qualitative analysis. The findings show that the Notion-based Islamic Religious Education e-module received a positive student response, with an overall mean score of 3.86 in the high category. The paired sample t-test showed statistically significant increases in learning motivation from 3.80 to 3.87, learning independence from 3.82 to 3.95, and perceived ease of use from 3.64 to 3.74. The regression analysis indicated that use of the e-module and perceived ease of use were significant predictors of learning motivation, while learning motivation and perceived ease of use were significant predictors of learning independence. The findings suggest that Notion-based e-modules have potential to support more structured, interactive, and independent Islamic Religious Education learning. However, the results should be interpreted cautiously because this study used a one-group pretest-posttest design without a control group and relied on self-report data. This study offers an alternative model of Islamic Religious Education e-module development by using Notion as a digital learning environment that integrates learning materials, assignments, reflection activities, flexible access, and independent learning support.